Adopting SOLID Principles in Android Application Development: A Case Study and Best Practices - Nimisha Hake; Laxmipriya Heena Dip (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Developing and maintaining large-scale applications has become a daunting task with the rapid evolution of the Android ecosystem. This research examines the application of SOLID (Single Responsibility, Open/Closed, Liskov Substitution, Interface Segregation, and Dependency Inversion) principles in contemporary Android development. By the case study of Meta and an analysis of the application in top tech companies, the present research shares how SOLID principles can achieve better product quality, maintainability, and a positive outcome between your team. The study is based on a mixed-methodology, including qualitative and quantitative, analyzing the source code of 25 enterprise-grade Android applications, in-depth interviews with 50 senior professionals from top-tier technology companies, and code-metrics data for 24 months. We implemented it in Kotlin, taking advantage of the modern Android Jetpack ecosystem. The results of the study demonstrate dramatic increases in all aspects of software development. These include 45% reduction in technical debt, 89% increase in test coverage and 30% reduction in bug rate. A qualitative analysis indicates that teams report increased ease of code maintenance and ramp up of new team members. The research also highlights some of the barriers to applying SOLID: high learning curve, challenges convincing team members to adopt SOLID mindset. Our research contributes (1) a SOLID implementation framework for Android, empirically validated in four case studies. It also includes (2) metrics and tools for measuring adherence to SOLID principles, and (3) recommendations for resolving issues encountered during the implementation of these principles. These results have significant practical implications for mobile software industry practitioners and researchers